MIKROPROPAGASI TANAMAN TALAS BENENG (Xanthosoma undipes K. Koch) DENGAN PERLAKUAN BENZIL AMINOPURIN, TIAMIN, DAN ADENIN - Sari, Laela; Wulansari, Aida; Noorrohmah, Siti; Ermayanti, Tri Muji (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2019)
Micropropagation of Beneng Taro (Xanthosoma undipes K. Koch) with Benzyl Amino Purine, Thiamine, and Adenine TreatmentABSTRACTConventional production of Beneng taro seeds (Xanthosoma undipes K. Koch) is constrained by the limited number of tubers, thus an alternative solution is needed such as in vitro propagation. This study was aimed to obtain a micropropagation technique of Beneng taro on MS media with BAP, thiamine, and adenine treatment, and to determine its growth at the acclimatization stage. This research consisted of shoot multiplication and acclimatization. Shoot propagation was carried out on MS media with 8 treatments, namely ½MS and MS without addition of growth promoting substance, and MS with 1, 2 and 3 mg×L-1 BAP, with or without addition of 1 mg×L-1 thiamine and 2 mg×L-1 adenine. Each treatment was replicated four times, each consisting of four shoots. Growth observation was made from 1st to 5th week on petiole length, and number of shoots, leaves and roots. Acclimatization was carried out on soil media, compost, and husks in a ratio of 1: 1: 1. The results showed that the best media for shoot multiplication was MS + 1 mg×L-1 BAP + 1 mg×L-1 thiamine + 2 mg×L-1 adenine with an average of 3.5 shoots, while the best medium for the petiole length was ½MS with an average value of 6.97 cm. The results of acclimatization showed that 100% planlets survived, and plantlets grown on MS media + 3 mg×L-1 BAP had the highest number of shoots with an average of 4.2.Keywords: adenine, Beneng taro, benzil amino purine (BAP), micropropagation, thiamineABSTRAKPenyediaan bibit talas Beneng (Xanthosoma undipes K. Koch) secara konvensional terkendala terbatasnya jumlah umbi, sehingga perlu solusi alternatif, diantaranya melalui perbanyakan in vitro. Tujuan penelitian ini adalah untuk mendapatkan teknik mikropropagasi talas beneng pada media MS dengan perlakuan BAP, tiamin, adenin, dan untuk mengetahui pertumbuhannya pada tahap aklimatisasi. Penelitian ini meliputi perbanyakan tunas dan aklimatisasi. Perbanyakan tunas menggunakan media MS dengan 8 perlakuan yaitu ½MS dan MS tanpa penambahan zat pengatur tumbuh (ZPT), serta MS dengan 1, 2 dan 3 mg×L-1 BAP dengan atau tanpa penambahkan 1 mg×L-1 tiamin dan 2 mg×L-1 adenin. Setiap perlakuan mempunyai empat ulangan, setiap ulangan terdiri atas empat tunas. Pertumbuhan diamati mulai minggu ke-1 hingga ke-5 terhadap panjang petiol serta jumlah anakan, daun dan akar. Aklimatisasi dilakukan pada media tanah, kompos dan sekam dengan perbandingan 1:1:1. Hasil menunjukkan bahwa media terbaik perbanyakan tunas adalah MS + 1 mg×L-1 BAP + 1 mg×L-1 tiamin + 2 mg×L-1 adenin dengan rata-rata 3,5 tunas, sedangkan media terbaik untuk panjang tangkai daun adalah ½MS dengan nilai rata-rata 6,97 cm. Hasil aklimatisasi menunjukkan bahwa 100% planlet hidup dan planlet yang ditumbuhkan pada media MS + 3 mg×L-1 BAP mempunyai jumlah anakan terbanyak dengan rata-rata 4,2.Kata Kunci: adenine, benzil amino purin (BAP), mikropropagasi, talas Beneng, tiamine